Insuficiência renal crônica em cães - Silva, Andrea Ulisses Martins da [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The kidneys, for his anatomical and functional characteristics, are sensitive to affections that take the liberation of renal toxins or the blood supply, causing irreversible injuries to his renoparenchymal tissue that is substituted by fibrous tissue. Even after the resolution of the basic cause, there will be the loss of a significant number of his functional unity, renal adaptations will take place in the attempt of maintaining the renal function. These adaptations produce additional injuries, perpetuating to loss of renoparenchymal tissue and the reduction of the renal function. The renal insufficiency (IR) takes place after the loss of 3/4 of the number of his functional unities. Before the progression to the phase of IR, the animal shows up practically without symptoms, but for the gradual increase of the urinary and of the ingestion of water. The reduction of the degree of renal function leads to alterations system compensatory for the accumulation of substances that would suffer renal excretion. The progression of IR leads to the phase of the syndrome urêmica. In this phase the animal presents innumerable clinical signs that can take it to the death. The treatment is symptomatic and dietetic, but depending on the phase not much efficient. Because of being progressive and insidious, the IRC demands the preparation of campaigns and programs of explanation for the veterinary doctors who aim for the consciousness and/or sensibility of the owners to carry out periodic examinations of selection that precociously detect the renal dysfunction. The diagnosis in the beginning IR enables the efficiency of the treatment in stop or slowing his progression, extending the time and quality of life of the patient

Os rins, por suas características anatômicas e funcionais, são sensíveis a afecções que levem a liberação de nefrotoxinas ou a isquemia renal, causando lesões irreversíveis ao seu parênquima que é substituído por tecido fibroso. Mesmo após a resolução da causa de base, se houver a perda de um número significativo da sua unidade funcional, ocorrerão adaptações renais na tentativa de manter a função renal. Essas adaptações geram lesões adicionais, perpetuando a perda de parênquima renal e a diminuição da função renal. A insuficiência renal (IR) ocorre após a perda de três quartos do número de suas unidades funcionais. Antes da progressão ao estágio de IR, o animal apresenta-se praticamente assintomático, a não ser pelo gradativo aumento da diurese e da ingestão de água. A diminuição do grau de função renal leva a alterações sistêmicas compensatórias pelo acúmulo de substâncias que sofreriam excreção renal. A progressão da IR leva ao estágio da síndrome urêmica. Neste estágio o animal apresenta inumeráveis sinais clínicos que podem levá-lo à morte. O tratamento é sintomático e dietético, mas dependendo do estágio pouco eficiente. A IRC por ser progressiva e insidiosa, exige a elaboração de campanhas e programas de esclarecimento pelos médicos veterinários que visem à conscientização e/ou sensibilização dos proprietários para realizarem exames periódicos de triagem que detectem precocemente a disfunção renal. O diagnóstico no início IR predispõe a eficácia do tratamento em estacionar ou desacelerar a sua progressão, prolongando o tempo e a qualidade de vida do paciente
Keywords: Cão - Doenças; Insuficiencia renal cronica; Hipertensão renal; Uremia; Dog - diseases